Prevalence and clinical characteristics of body dysmorphic disorder in adolescent inpatient psychiatric patients—a pilot study. (4th July 2019) - Jafferany, Mohammad; Osuagwu, Ferdnand C.; Khalid, Zaira; Oberbarnscheidt, Thersilla; Roy, Nikita
Abstract: Background: Body dysmorphic disorder (BDD) is preoccupation with perceived body defects leading to distress and impairment in social functioning. Most of adolescent BDD literature has been done on patients within the outpatient setting with prior versions of DSM with dearth of information about BDD and comorbid psychiatric conditions among adolescents within the inpatient setting. Aims: This pilot study evaluated the prevalence rate, clinical characteristics in adolescent BDD compared to non-BDD adolescents in a psychiatric in patient setting in addition to their comorbid issues like anxiety, OCD, ADHD and substance abuse. Methods: Forty-five consecutively admitted adolescent patients participated with 17 meeting the DSM 5 criteria for BDD while 28 did not. Patients were asked four questions designed around the DSM-5 criteria for BDD after which they were asked to complete questionnaires like BDDQ child and adolescent version, BDDM, Multiaxial Anxiety Scale for Children, Children's Depression Inventory, Y-BOCS and Vanderbilt ADHD rating scales. Results: Seventeen participants had BDD. Mean age of BDD patients was 13.1 while non-BDD was 12.4. Male patients with BDD were seven (41%) while female BDD patients were 10 (58.8%). Anxiety, depression, OCD and substance use disorders were common comorbid diagnoses. Majority of patients in the BDD group classified their BDD as a severe problem with more BDD, patient's considering suicide because of their BDD. Discussion: BDD is present in adolescents admitted in inpatient psychiatric hospital with more female patients endorsing BDD versus their male counterparts. Patients with BDD are more likely to endorse more comorbid psychiatric issues such as anxiety, OCD, ADHD and substance abuse.